A deterministic breakup model for Euler–Lagrange simulations of turbulent microbubble-laden flows. (February 2020) - Hoppe, F.; Breuer, M.
Highlights: A deterministic and viable breakup model for microbubble-laden turbulent flows. Transfer from the Euler-Euler method to the Euler-Lagrange approach. Deterministic estimation of the size of arising daughter bubbles. Physically motivated model for the separation axis and separation velocity. Time lag between two successive breakup processes proposed. Abstract: The present study is concerned with breakup models for microbubbles in turbulent flows. Analyzing the different physical mechanisms responsible for breakup based on a literature review, breakage due to turbulent fluctuations in the inertial subrange is identified as the most important one. Widely used breakup models for this mechanism are discussed concerning their advantages and drawbacks with special emphasis on thoughts how these models developed in the Euler-Euler context can be transferred into the Euler-Lagrange approach favored in this study. The most promising model is chosen as a basis and then implemented in an efficient bubble tracking scheme relying on the large-eddy simulation technique. The size of the daughter bubbles is deterministically estimated based on the breakup mechanism. Furthermore, a physically motivated model for the axis along which bubbles separate and for the separation velocity of the daughter bubbles is developed. Lastly, an estimate of the time lag between two successive breakup processes is provided. The simulation methodology is validated against an experimental study by Martínez-Bazán et al. (1999) investigating bubble breakup within a turbulent jet flow. The predicted results are found to be in reasonable agreement with the measurements. Furthermore, the effect of coalescence and other properties of the bubbles on the breakup behavior is investigated.